2020
DOI: 10.1007/s00128-020-02872-3
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Accumulation and the Effects of Long-Term Dietary Copper Contamination on Osmoregulation in the Mudflat Fiddler Crab Minuca rapax (Crustacea, Ocypodidae)

Abstract: We examined copper accumulation in the hemolymph, gills and hepatopancreas, and hemolymph osmolality, Na + and Cl − concentrations, together with gill Na + /K + -ATPase and carbonic anhydrase activities, after dietary copper delivery (0, 100 or 500 Cu µg g −1 ) for 12 days in a fiddler crab, Minuca rapax. In contaminated crabs, copper concentration decreased in the hemolymph and hepatopancreas, but increased in the gills. Hemolymph osmolality and gill Na + /K + -ATPase activity increased while hemolymph [Na + … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 64 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Harayashiki et al, (2018) measured the CAT and GST activities in Penaeus monidon Fabricius, 1798 juveniles fed on food contaminated with mercuric chloride and observed that it caused oxidative stress. Similarly, Capparelli et al (2020) observed that the GST activity was higher in the hepatopancreas of the fiddler crab Uca rapax (Smith, 1870) (now Minuca rapax) exposed to copper when compared to control group. In our study, we also observed higher activity of GST in animals exposed to water from the SB1.…”
Section: Discussionmentioning
confidence: 88%
“…Harayashiki et al, (2018) measured the CAT and GST activities in Penaeus monidon Fabricius, 1798 juveniles fed on food contaminated with mercuric chloride and observed that it caused oxidative stress. Similarly, Capparelli et al (2020) observed that the GST activity was higher in the hepatopancreas of the fiddler crab Uca rapax (Smith, 1870) (now Minuca rapax) exposed to copper when compared to control group. In our study, we also observed higher activity of GST in animals exposed to water from the SB1.…”
Section: Discussionmentioning
confidence: 88%